Changes in the upper airway following induction of anaesthesia: a prospective observational study protocol to determine the use of ultrasound in the assessment of a difficult airway in China - Dong, Fang; Wang, Yong; Wang, Xia; Zhao, Huanyi; Ma, Wuhua (BMJ open, 2019)
IntroductionDifficult airway management is closely related to the safety and quality of medical care. However, the low incidence of correct prediction of difficult airway in clinical screening tests presents physicians with a dilemma. Depressed airway neuromuscular tension during sleep and anaesthesia tends to cause collapse of fragile parts of the upper airway. Although previous studies have confirmed that anterior cervical tissue thickness is associated with difficult airways, there is no evidence to support a correlation between a difficult airway and specific patterns or findings of anaesthesia-induced airway collapse. Thus, this study aims to examine changes in airway dimensions before and after induction of general anaesthesia to explore whether it could provide useful information regarding the specific anatomic changes occurring which may cause difficult airways.Methods and analysisThis will be a single-centre prospective observational single-blinded study, conducted in a tertiary teaching hospital in Guangzhou, China. Subjects will be recruited from patients (aged 18–65 years) scheduled for elective surgery under general anaesthesia. Sonographic measurement will be performed to detect changes in the thickness of the anterior cervical soft tissue before and after anaesthetic induction. Based on the resulting data distribution, analyses will initially compare these changes using a paired t-test or the Wilcoxon signed-rank test. The correlation of sonographic changes and Cormack–Lehane grade will be evaluated by using receiver-operating characteristic curves to detect the sensitivity and specificity of a measurement for detecting difficulties. Linear stepwise regression analysis will be used to assess the correlation between airway changes and demographic variables as well as clinical tests.Ethics and disseminationEthical approval has been obtained from the Ethics Committee of the First Affiliated Hospital of Guangzhou University of Chinese Medicine (ZYYECK (2018) 041). The results will be disseminated through conference presentations, professional journals and peer-reviewed publications.Trial registration numberChiCTR1900021123; Pre-results.